Development Of Physical Training Patterns At Husein Sastranegara Air Force Base To Improve Physical Fitness To Support The Tasks Of The Air Force - Dwi Ariyanti, Devi; Eko, Bambang; Arman, Andi (CV RIFAINSTITUT, 2025)
Physical training is a crucial element in preparing Indonesian Air Force personnel to face the high physical and mental demands of their duties. This article examines the development of physical training at Husein Sastranegara Air Base and its impact on improving the physical fitness of personnel. Through a qualitative approach, this study collected data from various sources, including in-depth interviews with physical trainers, personnel, and medical staff, as well as document analysis related to the physical training program. The study results indicate that the development of a structured and scientifically-based physical training program has a significant impact on the physical fitness of personnel. Programs that include cardiovascular, strength, agility, and flexibility exercises, tailored to the operational needs of the Indonesian Air Force, can enhance the overall physical performance of personnel. Moreover, active participation in these programs also contributes to reducing injury rates and improving mental health. The implications of these findings suggest that investment in facilities and resources for physical training, as well as the development of a comprehensive curriculum, are essential steps to support the Indonesian Air Force's mission. This article recommends increased budget allocation and attention to physical training as an integral part of human resource development strategies at Husein Sastranegara Air Base.